2020
DOI: 10.1088/1742-6596/1661/1/012108
|View full text |Cite
|
Sign up to set email alerts
|

Development of autonomous traction system of electric vehicle with electronic differential and fuzzy control system

Abstract: The article discusses the optimal layout of an autonomous vehicle traction system. In modern society, a special place is occupied by environmental issues. From year to year, a huge amount of statistics is published that reflect the scale of the damage that human products cause to the environment. Today, the main “pest” on the planet is surely cars with an internal combustion engine. At the same time, a complete rejection of motor transport, both in Russia and in the world, is impossible, because the life of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Electric vehicle technology is often seen as an enabling platform that would facilitate the integration of other branches of CASE technologies, because the redesign of vehicle's electrical systems are required in most applications [53]. There are many formats of EVs, but battery electric vehicles (BEVs) have recently gained a lot of momentum in the market.…”
Section: Extension To Case Technologiesmentioning
confidence: 99%
“…Electric vehicle technology is often seen as an enabling platform that would facilitate the integration of other branches of CASE technologies, because the redesign of vehicle's electrical systems are required in most applications [53]. There are many formats of EVs, but battery electric vehicles (BEVs) have recently gained a lot of momentum in the market.…”
Section: Extension To Case Technologiesmentioning
confidence: 99%
“…Popov et al In their study, they performed EDS control for 3 different power transmission topologies of electric vehicles using fuzzy logic in Simulink. It has been observed that a strong control and energy performance optimization is provided thanks to the fuzzy logic algorithm [11].…”
Section: Figurementioning
confidence: 99%